Participatory Empowerment Model: Integrating Religious Social Capital and the Digital Economic Capacity of MSMEs - Rahel, Muhammad; Huda, Nurul; Ariyani, Ariyani; Farhani, Ummi; Ariyana, Ariyana; Hafid, Moh.; Zaki, Mirsa Gulam; Hazin, Moh (TRANSFORMASI : JURNAL PENGABDIAN PADA MASYARAKAT, 2025)
The community of Carabaka Village in the Tambak subdistrict of Bawean Island possesses strong religious social capital, yet it faces challenges in optimizing its local economic potential and digital capacity. This community service initiative implements a participatory empowerment model integrating religious social capital and enhancing digital economic capacity for micro, small, and medium enterprises (MSMEs). Using the Participatory Action Research (PAR) method, the program was implemented collaboratively by KKN students, Field Supervisors (DPL), and all Carabaka Village community members, including MSMEs, religious leaders, youth, and women's organizations. The results of the community service demonstrate that strengthening religious social capital through activities such as collective efforts to renovate the mosque, fundraising amounting to Rp 9,900,000, and regular religious activities successfully enhanced social cohesion and the spirit of participation among residents. Concurrently, economic empowerment for MSMEs based on local wisdom, such as tamarind, cassava chips, and soybeans, was enhanced through branding and digital marketing training using Canva and CapCut, as well as packaging assistance and guidance in obtaining a Business Identification Number (NIB). This program shows that integrating religious social capital with digital economic capacity through a participatory approach effectively creates holistic, sustainable community empowerment.